An Approach to Model the Active Site of Peptidglycine‐α‐hydroxylating monooxygenase (PHM). Issue 8 (30th April 2013) - Hoppe, Tobias; Josephs, Patrick; Kempf, Natascha; Wölper, Christoph; Schindler, Siegfried; Neuba, Adam; Henkel, Gerald
Abstract The copper(I) and copper(II) complexes [Cu((TMGet)2NetSEt)]BPh4 (1·BPh4) and [Cu((TMGet)2NetSEt)Cl]Cl (2·Cl) with (TMGet)2NetSEt = ((Me2N)2C=NCH2CH2)2NCH2CH2SEt were synthesized and structurally characterized as a model system for the copper enzyme PHM, a monooxygenase involved in the activation of peptide hormones and neuropeptides. The reaction of the copper(I) complex 1·BPh4 with dioxygen has been studied using low temperature stopped‐flow methods. However, in contrast to PHM no formation of an end‐on copper superoxido complex could be observed. Instead an equilibrium between a bis‐μ‐oxo and a side‐on peroxide complex was detected spectroscopically.